Stability of Inhaled Ciprofloxacin-Loaded Poly(2-ethyl-2-oxazoline) Nanoparticle Dry Powder Inhaler Formulation in High Stressed Conditions - Mohammad Zaidur Rahman Sabuj; Md Abdur Rashid; Tim R. Dargaville; Nazrul Islam (MDPI AG, 2022)
In this study, the stability of ciprofloxacin (CIP)-loaded poly(2-ethyl-2-oxazoline) (PEtOx) nanoparticles (NPs) was investigated at normal and high stressed conditions. The blank NPs were used to understand the intrinsic physicochemical properties of the polymer NPs under these storage conditions. The formulated NPs were prepared by a coassembly reaction and dried by lyophilization. The powder NPs were stored at controlled room temperature (25 °C) with normal relative humidity (RH) (43%) and high temperature (40 °C) and RH (75%). The stored samples were analyzed by determining the particle sizes, morphology, solid-state properties, thermal behavior, drug-polymer interactions, and aerosol performances over six months. The chemical stability of the formulations was determined by X-ray diffraction, attenuated total refection-Fourier transform infrared (ATR-FTIR), and high-performance liquid chromatography (HPLC) over six months under both conditions. The particle size of the blank PEtOx NPs significantly (p < 0.05) increased from 195.4 nm to 202.7 nm after 3 months at 40 °C/75% RH due to the moisture absorption from high RH; however, no significant increase was observed afterward. On the other hand, the sizes of CIP-loaded PEtOx NPs significantly (p < 0.05) reduced from 200.2 nm to 126.3 nm after 6 months at 40 °C/75% RH. In addition, the scanning electron microscopy (SEM) images revealed that the surfaces of CIP-loaded PEtOx NPs become smoother after 3 months of storage due to the decay of surface drugs compared to the freshly prepared NPs. However, transmission electron microscopy (TEM) images could not provide much information on drug decay from the nanoparticle's surfaces. The fine particle fraction (FPF) of CIP-loaded PEtOx NPs dropped significantly (p < 0.05) after three months at 25 °C/43% RH and 40 °C/75% RH conditions. The reduced FPF of CIP-loaded PEtOx NPs occurred due to the drug decay from the polymeric surface and blank PEtOx NPs due to the aggregations of the NPs at high temperatures and RH. Although the aerosolization properties of the prepared CIP-loaded PEtOx NPs were reduced, all formulations were chemically stable in the experimental conditions.